Penerapan Model Pembelajaran Jigsaw Untuk Meningkatkan Aktivitas Belajar Pada Matakuliah Bahasa Inggris SD - Yuliani Sepe Wangge (Program Studi Pendidikan Ekonomi, Universitas Flores, 2020)
This study aims to increase study activities in elementary school English courses through the use of the Jigsaw learning models in the third semester students of Flores University PGSD study program. This research is a class action research that uses the Kemmis & Taggart model. The subject in this study was 35 third semester students. Data collection techniques are performed by observation and documentation. Data is analyzed in a qualitative descriptive way. The results showed that learning activities in elementary school English courses through the use of Jigsaw learning models had increased. The percentage of oral activity on the first cycle increased from 48.57 with enough categories, to 77.85 with good categories on the second cycle. The listening activity on the first cycle is 52.85 with enough categories, increasing to 75.71 with good categories on the second cycle. Writing activity on the first cycle is increased from a category with a percentage of 54.28 to 90 with excellent categories on the second cycle. Percentage of mental activity increased from 57.14 by category enough to 92.85 with excellent categories on the second cycle, and emotional activity increased from 53.57 by category enough to be 85.57 with excellent categories on the second cycle. Based on the results it can be concluded that use of Jigsaw learning models can increase learning activity in elementary school English courses.